2015
DOI: 10.1111/hequ.12084
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of the Influencing Factors for International Academic Mobility of Chinese University Students

Abstract: This research aims to understand the factors influencing international academic mobility within the Chinese higher education context. The inventory of University Students’ Perceptions of Influencing Factors for International Academic Mobility was developed and tested to enquire about Chinese university students’ perceptions of factors influencing their decisions on international academic mobility. The findings reveal that ‘mobility cost’, ‘quality of host institutions’, ‘future career prospects’, ‘financial ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 20 publications
2
41
0
3
Order By: Relevance
“…Considering the subject in question, its relevance in the academic world is perceived by an empirical study and a contribution to existing literature, however, it is necessary to cover other identified gaps and also to be exploited by different researchers.Through the theoretical review, it is possible to identify and analyze the international mobility in differ-ent countries and compare it with the reality of this particular case, especially to the specific cases that adopt the "push-pull" fundamentals. Similarities of some of the attraction factors of these studies are observed, for example: Mazzarol & Goffrey (2002) with the importance of language, more flexible selection processes and good reputation in the country of origin after the experience, Li & The importance of the environment (family and friends) for decision making, and finally Molly (2007) and Cao, Zhu & Meng (2016) with Mey & Bray (2007) "social status", Bodycott (2009) and Chen & Zimitat the concern related to the cost of living. In particular, the study by Altbach (1998) was fundamental for the organization of the data collection instrument (semi-structured questionnaire) and for the identification and analysis of the attractiveness factors of Brazilian students in Spain, where it was noted interviews the importance of the factors of attraction such as: interest in the country Spain for studies abroad as a highly relevant option, scholarship systems, the influence of the environment, the cost of mobility and approach to the language of origin.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Considering the subject in question, its relevance in the academic world is perceived by an empirical study and a contribution to existing literature, however, it is necessary to cover other identified gaps and also to be exploited by different researchers.Through the theoretical review, it is possible to identify and analyze the international mobility in differ-ent countries and compare it with the reality of this particular case, especially to the specific cases that adopt the "push-pull" fundamentals. Similarities of some of the attraction factors of these studies are observed, for example: Mazzarol & Goffrey (2002) with the importance of language, more flexible selection processes and good reputation in the country of origin after the experience, Li & The importance of the environment (family and friends) for decision making, and finally Molly (2007) and Cao, Zhu & Meng (2016) with Mey & Bray (2007) "social status", Bodycott (2009) and Chen & Zimitat the concern related to the cost of living. In particular, the study by Altbach (1998) was fundamental for the organization of the data collection instrument (semi-structured questionnaire) and for the identification and analysis of the attractiveness factors of Brazilian students in Spain, where it was noted interviews the importance of the factors of attraction such as: interest in the country Spain for studies abroad as a highly relevant option, scholarship systems, the influence of the environment, the cost of mobility and approach to the language of origin.…”
Section: Discussionmentioning
confidence: 63%
“…The main authors and attraction factors identified in their studies: Altbach (1998) cost of mobility, employment rate in the host country, geographic distance, environmental environment, quality of institutions, financial support, perspectives of professional future, economic situation of the country of origin, language, intercultural training of the institution of origin, the family, interest in mobility - Mazzarol & Geoffrey (2002) the language, an estimate that a course conducted in a foreign country is better than in your home country, the ease of access to the course and, mainly, the reputation that this experience can bring in the future -Kazlauskienė & Rinkevičius (2006) "brain-drain" Professional attraction in foreign countries, socioeconomic conditions. Other factors, such as ecological conditions and family reunification, play a much smaller role in this phenomenon of brain drain -Mei Li & Mark Bray (2007) the motivations in pose of the academic and professional growth, the economic benefit, the individual internationalization and the improvement of the social status - Molly (2007) Future migration opportunities after graduation education, high quality courses and the cost of living -Bodycott (2009) significant differences were found between the role and approach of students and their parents in the first and last stage of decision making (tradition and values) -Wilkins, Balakrishnan & Huisman (2012) the study incorporates two different sets of "push-pull" factors and sought to better understand current and potential students, in order to implement segmentation techniques in their marketing activities and finally Cao, Zhu & Meng (2016) future career prospects, the quality of institutions, the cost of mobility and climate in the host country. Geographic distance emerged as an unfavorable attraction and a significant risk factor.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…As shown in Table , students in social sciences and humanities reported gaining higher global competence in all three dimensions than students in physics and engineering and life sciences. This finding was mirrored in previous studies that students in social sciences and humanities are traditionally more interested in studying abroad and have a higher sense of global citizenship (Lincoln Commission, ; Hoffa, ; Cao et al ., ). A possible explanation is the different educational background and curricular settings.…”
Section: Results Discussion and Implicationsmentioning
confidence: 97%
“…While some studies have looked into students' motives and perceived barriers (e.g. Cao, Zhu & Meng, 2016), others have concentrated on personality traits (Zimmermann & Neyer, 2013) or socio-economic characteristics (Finger & Netz, 2016). These were used to predict the likelihood of students becoming academically mobile.…”
Section: Empirical Findingsmentioning
confidence: 99%